Importance of "historic sites" on Heard Island for protection of scientific resources and environmental management of a World Heritage site - E Lazer; Janet Hughes (Papers and Proceedings of the Royal Society of Tasmania, 2000)
Heard Island has important historic sites relating to the hunting of elephant seals and various scientific activities, which are noted in the World Heritage citation for the island. Some, especially sealing sites, are generally acknowledged to have historic value, but the value of later sites, such as the first ANARE base at Atlas Cove, is debated, due to its recent date, unattractive appearance, rapid deterioration and hazards to wildlife. The authors believe that Atlas Cove is significant to Australia's Antarctic history, but this does not necessarily require that all elements of the site must be preserved in situ. The potential historical value of this site is briefly reviewed; the value of comparative studies of historical, archaeological and materials observation information on historic sites on other Subantarctic islands is also considered. Documentation of these aspects of the sites is essential, certainly before any "clean up" is carried out at Adas Cove since it will produce information to assist in environmental management and may benefit scientific research. Identification of the scientific artefacts and achievements should be an essential part of documentation of Subantarctic sites, but generally has not been given significant attention by archeologists. For development of a statement of significance for Atlas Cove, it is vital.